AL-AF’ÂL AL-TAWJÎHIYAH LADÂ AL-MU’ALLIMÎN FÎ AL-TAFÂ’UL AL-SHAFFÎ ATSNÂ TA’LÎM AL-LUGHAH AL-‘ARABIYAH ‘ALÂ DHAU NAZHARIYAH SINCLAIR WA COULTHARD - Qomariyah, Lailatul; Hasanah, Mamluatul (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This research examined the directive speech acts of Arabic teacher in the teaching learning process: the perspective of Sinclair and Coulthard. The study focused on: (1) the forms of directive speech acts in the teaching learning process of Arabic class at Islamic Senior High School in Al Munawaroh. This research was conducted by qualitative case approach. The data of this research was the directive speech acts of teacher. The data were collected from recording observation and interview and was analyzed by interactive model analysis.The findings consisted of the form of directive speech acts in the teaching learning process of Arabic class containing 3 forms. There were imperative, interogative, and declarative. From this study, it is expected that Arabic language teachers are able to use isim fi’il amr